2022
DOI: 10.1155/2022/8878923
|View full text |Cite
|
Sign up to set email alerts
|

Orientin Prolongs the Longevity of Caenorhabditis elegans and Postpones the Development of Neurodegenerative Diseases via Nutrition Sensing and Cellular Protective Pathways

Abstract: Age is the major risk factor for most of the deadliest diseases. Developing small molecule drugs with antiaging effects could improve the health of aged people and retard the onset and progress of aging-associated disorders. Bioactive secondary metabolites from medicinal plants are the main source for development of medication. Orientin is a water-soluble flavonoid monomer compound widely found in many medicinal plants. Orientin inhibits fat production, antioxidation, and anti-inflammatory activities. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 76 publications
0
1
0
Order By: Relevance
“…Moreover, flavonoid compounds improved heat, oxidative, and pathogenic stress resistances to delay the aging of C. elegans. This was achieved through the activation of stress responses, including HSF-1-mediated heat shock response, SKN-1-mediated xenobiotic and oxidation response, mitochondria unfolded response, endoplasmic unfolded protein response, and increased autophagy activity [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, flavonoid compounds improved heat, oxidative, and pathogenic stress resistances to delay the aging of C. elegans. This was achieved through the activation of stress responses, including HSF-1-mediated heat shock response, SKN-1-mediated xenobiotic and oxidation response, mitochondria unfolded response, endoplasmic unfolded protein response, and increased autophagy activity [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…This behavior was not observed in the nematodes fed L. plantarum DSM20174. Moreover, several reports showed that delaying C. elegans aging is associated with an enhanced resistance to oxidative stress [52,53], suggesting a plausible mode of action in L. plantarum PFA2018AU. Furthermore, worms do not have adaptive immunity but only innate immune defences, like human pathways [17].…”
Section: Discussionmentioning
confidence: 99%